2004
DOI: 10.1614/wt-03-136r
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Tillage, Rye Residues, and Herbicides Influence Weed Suppression and Yield of Pumpkins

Abstract: Field experiments were conducted to study the effects of various tillage and mulching practices on fruit maturity and weed suppression in pumpkins. Conventional tillage (CT), disking, no tillage with rye removed (RR), no tillage with standing rye (SR), and strip tillage (ST) were evaluated with and without ethalfluralin plus halosulfuron (1.5 plus 0.036 kg ai/ha, respectively) applied preemergence. In 2001, when heavy rain after herbicide application caused significant crop injury, the herbicides delayed matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Cover crop mulch systems modify the microenvironment, which has an impact on weed populations and vegetable crop yields (Masiunas 1998). Although the combination of NT and cover-cropping practices have certain advantages over traditional tillage (e.g., plowing and disking of soil), there has been limited research in vegetable crops, particularly when used in conjunction with chemical weed control (Rapp et al 2004). Cover crops are often integrated into NT production systems for their weed suppressive ability and numerous researchers have attempted to use cover crops as a method for weed control in vegetable crop production.…”
Section: Cover Crop Based Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cover crop mulch systems modify the microenvironment, which has an impact on weed populations and vegetable crop yields (Masiunas 1998). Although the combination of NT and cover-cropping practices have certain advantages over traditional tillage (e.g., plowing and disking of soil), there has been limited research in vegetable crops, particularly when used in conjunction with chemical weed control (Rapp et al 2004). Cover crops are often integrated into NT production systems for their weed suppressive ability and numerous researchers have attempted to use cover crops as a method for weed control in vegetable crop production.…”
Section: Cover Crop Based Systemsmentioning
confidence: 99%
“…Several studies have all indicated that NT and CT produce comparable pumpkin yields when sufficient weed control is achieved in NT production systems (Galloway & Weston 1996, Rapp et al 2004. Pumpkin vegetation will provide some soil shading and weed suppression once vines form across the soil surface, but other weed control measures are generally necessary to achieve adequate weed control in NT pumpkin production.…”
Section: Pumpkinmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Chikoye et al (2007) reported that rimsulfuron did not cause any visible phytotoxicity on the maize at any dosage. Moreover, there are limited published data on the combination effects of tillage and herbicides application on weed flora and growth of crops (Rapp et al, 2007;Ritter and Menbere, 2001;Streit et al, 2002).…”
Section: Introductionmentioning
confidence: 99%